The mental representation of the human gait in young and older adults - Stöckel, Tino; Jacksteit, Robert; Behrens, Martin; Skripitz, Ralf; Bader, Rainer; Mau-Moeller, Anett (Frontiers in Psychology, 2015)
The link between mental representation (MREP) structures and motor performance has been evidenced for a great variety of movement skills, but not for the human gait. Therefore the present study sought to examine the cognitive memory structures underlying the human gait in young and older adults. In a first experiment, gait parameters at comfortable gait speed (OptoGait) were compared with gait-specific MREPs (structural dimension analysis of MREP; SDA-M) in 36 young adults. Participants were divided into a slow- and fast-walking group. The proven relationship between gait speed and executive functions such as working memory led to the hypothesis that gait pattern and MREP differ between slow- and fast-walking adults. In a second experiment, gait performance and MREPs were compared between 24 young (27.9yrs) and 24 elderly (60.1yrs) participants. As age-related declines in gait performance occur from the 7th decade of life onward, we hypothesised that gait parameters would not be affected until the age of 60 years accompanied by unchanged MREP. Data of Experiment 1 revealed that gait parameters and MREPs differed significantly between slow and fast walkers. Notably, eleven previously-incurred musculoskeletal injuries were documented for the slow walkers but only two injuries and one disorder for fast walkers. Experiment 2 revealed no age-related differences in gait parameters or MREPs between healthy young and older adults. In conclusion, the differences in gait parameters associated with lower comfortable gait speeds are reflected by differences in MREPs, whereby SDA-M data indicate that the single limb support phase may serve as a critical functional period. These differences probably resulted from previously-incurred musculoskeletal injuries. Our data further indicate that the human gait and its MREP are stable until the age of 60. SDA-M may be considered as a valuable clinical tool for diagnosis of gait abnormalities and monitoring of therapeutic effectiveness.